Exploring the Interaction Objectives of Digital New Venture Groups in Entrepreneurial Education (Analysis of Multiple Goals Theory) - Aji, Imanuel Deny Krisna; Karsidi, Ravik; Nurhaeni, Ismi Dwi Astuti; Sudarmo (Jogjakarta Communication Conference (JCC), 2025)
Educating students in entrepreneurship is a way to enhance the number of entrepreneurs. At the higher education level, it is executed by incorporating entrepreneurship courses into the curriculum with particular emphasis. Attention must be directed towards various stakeholders, particularly the institutions that facilitate entrepreneurship education, to ensure that the program enhances not only quantitative outcomes (the number of new student ventures) but also qualitative outcomes (sustainable new ventures), even after the completion of the educational process. The presence of multiple objectives among members of the digital new venture group for interaction is a significant issue that requires additional investigation in this study. This research uses the Multiple Goals Theory framework in interpersonal communication to delineate the objectives of interaction as perceived by each member of the new digital venture group. The study employed a quasi-qualitative methodology, incorporating in-depth interviews, observations, and recording, involving 15 student participants from the new digital venture group and the facilitator. Every student in the new digital venture group possesses interaction objectives classified into three categories: instrumental goals, interpersonal goals, and identification goals. This study demonstrates that Multiple Goals Theory indicates the interaction objectives of students in the new digital venture group encompass primary goals, mostly categorized as instrumental goals, specifically aimed at achieving an optimal course evaluation and developing a new venture. In this study, secondary interaction goals, which are theoretically intended to impede the attainment of primary interaction goals, instead facilitate the fulfillment of those basic goals.